Peranan Lembaga Keuangan Dalam Meminimalisir Ketimpangan Pendapatan Di Kabupaten Sumbawa - Siti Nur Hidayati; Selmiana Sapitri; Liawati; Saindra (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2024)
Income inequality is still a problem in the Indonesian economy, especially in   Sumbawa Regency. In order to realize the welfare of the community evenly, the Sumbawa district government seeks to reduce the income inequality rate between sub-districts in Sumbawa district. Community financial institutions are expected to help the economy of the poor so that economic income equality will be realized so as to minimize inequality. The purpose of the study was to determine the role of financial institutions in minimizing income inequality.   In Sumbawa Regency. This research is a type of qualitative research. The results showed that financial institutions play a significant role in income inequality in Sumbawa Regency